Cover Picture: Biocatalytic Reduction of HMF to 2, 5‐Bis(hydroxymethyl)furan by HMF‐Tolerant Whole Cells (ChemSusChem 2/2017). Issue 2 (12th January 2017) - Li, Yan‐Mei; Zhang, Xue‐Ying; Li, Ning; Xu, Pei; Lou, Wen‐Yong; Zong, Min‐Hua
Abstract : The Cover picture shows the biocatalytic transformation of 5‐hydroxymethylfurfural (HMF), which is an important bio‐based platform chemical, to 2, 5‐bis(hydroxymethyl)furan. Such upgrading to high‐value products is of currently of considerable interest but difficult to achieve. In this case, a new highly HMF‐tolerant yeast strain—Meyerozyma guilliermondii SC1103 was isolated and used for the biocatalytic reduction of HMF using its resting cells over a wide pH range. Co‐substrates exerted a significant effect on the catalytic activity and selectivity of microbial cells as well as their HMF‐tolerant levels, whereas a nitrogen source and mineral salts had no such effects. More details can be found in the Full Paper by Li et al. onpage 372 in Issue 2, 2017 (DOI:10.1002/cssc.201601426 ).